Spintherobolus papilliferus Eigenmann, 1911: a redescoberta de uma espécie de peixe ameaçada de extinção (Characiformes, Characidae) - Bento, Rodrigo de Moura Manoel (Universidade Federal de São Carlos, 2021)
The Atlantic Forest is one of the most relevant forests worldwide, housing approximately 5% of all vertebrate diversity and 7% of known species of plants. There are over 350 fish species within its rivers and streams, roughly 38% of which are endemic of this biome. Such is the case of Spintherobolus papilliferus, a critically endangered tropical Characidae. S. papilliferus is defined by five autapomorphies and is currently classified as sister to all other species of the genus. Until recently, few specimens of S. papilliferus were known, mostly from sparse locations in the Upper Rio Tietê basin around the metropolitan area of São Paulo, and from an affluent of Rio Itapanhaú, a coastal stream in the city of Bertioga, SP. In 2019, specimens of S. papilliferus were registered from Rio Ribeira de Iguape basin in Juquitiba, SP, representing a new record in the geographic distribution of the species. In the present study, 17 morphometric and 6 meristic data from all eight specimens were analysed, confirming its identification. For comparison, 10 specimens from the Upper Rio Tietê and 7 from Rio Itapanhaú previously deposited in ichthyological collections were also analysed. A great overlap in the morphological data from the three populations was detected, except for eye diameter, body depth and caudal-peduncle depth. A MANOVA analysis revealed that the Ribeira de Iguape population differs significantly from the other two in these characters, showing less deep body and caudal peduncle. We suggest that these morphological differences may be due to environmental selective pressures, at least partially, since Rio Ribeira drainage is marked by fast waters which can influence the shape of fish bodies over time. In addition, we present herein a hypothesis for the disjunct distribution of S. papilliferus in the light of recent geological events such as headwater capture. Future genetic studies may bring new evidence concerning the evolution and biogeography of the genus and its species.
Spintherobolus papilliferus Eigenmann, 1911: the rediscovery of a threathened fish species (Charciformes, Characidae)
Keywords: piquira-cabeçuda; taxonomia; biogeografia; Juquitiba; Rio Juquiá; CIENCIAS BIOLOGICAS::ZOOLOGIA::TAXONOMIA DOS GRUPOS RECENTES